2022
DOI: 10.3390/cancers14041089
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art and Future Implications of SH003: Acting as a Therapeutic Anticancer Agent

Abstract: Cancer ranks as the first leading cause of death globally. Despite the various types of cancer treatments, negative aspects of the treatments, such as side effects and drug resistance, have been a continuous dilemma for patients. Thus, natural compounds and herbal medicines have earned profound interest as chemopreventive agents for reducing burden for patients. SH003, a novel herbal medicine containing Astragalus membranaceus, Angelica gigas, and Trichosanthes kirilowii, showed the potential to act as an anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…SH003 is a novel herbal mixture for the treatment of several cancers including nonsmall cell lung cancer (NSCLC) [14][15][16][17][18][19][20][21][22][23][24][25]. The molecular mechanism of SH003 in cancer inhibition is associated with both the induction of cell cycle arrest, apoptosis, and autophagy and the suppression of tumor angiogenesis [26]. Recently, we demonstrated that SH003 is a good partner to combine with docetaxel, a conventional chemotherapy medication, for the treatment of NSCLC patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…SH003 is a novel herbal mixture for the treatment of several cancers including nonsmall cell lung cancer (NSCLC) [14][15][16][17][18][19][20][21][22][23][24][25]. The molecular mechanism of SH003 in cancer inhibition is associated with both the induction of cell cycle arrest, apoptosis, and autophagy and the suppression of tumor angiogenesis [26]. Recently, we demonstrated that SH003 is a good partner to combine with docetaxel, a conventional chemotherapy medication, for the treatment of NSCLC patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…SH003 is a decoction of medicinal herbs consisting of Astragalus membranaceus, Angelica gigas, Trichosanthes Kirilowii. 62 PHY906 is a decoction of a mixture of 4-herbs, Scutellarin baicalensis Georgi, Glycyrrhiza uralensis Fisch, Paeonia lactiflora Pall, and Ziziphus jujuba Mill. 63 Besides, the aforementioned trials investigated DaHuang GanTsao Tang, Maekmoondong-tang, Xiang Bei Yang Rong Tang, Sheng-Yu-Tang, and others.…”
Section: Discussionmentioning
confidence: 99%
“…SH003 is a herbal mixture of Astragalus membranaceus , A . gigas , and trichosanthes Kirilowii , which are traditionally used in East Asian medicine and its first phase l clinical trial (NCT03081819 and NCT04360317) was performed to identify the maximum tolerated dose in patients with solid (maximum tolerated dose for SH003 administration alone confirmed the daily safe dose to be up to 4800 mg) (Lee et al, 2022). Another preparation of A .…”
Section: A Rapid Review Of the Clinical Trials Of Angelica Extractsmentioning
confidence: 99%
“…SH003 is a herbal mixture of Astragalus membranaceus, A. gigas, and trichosanthes Kirilowii, which are traditionally used in East Asian medicine and its first phase l clinical trial (NCT03081819 and NCT04360317) was performed to identify the maximum tolerated dose in patients with solid (maximum tolerated dose for SH003 administration alone confirmed the daily safe dose to be up to 4800 mg) (Lee et al, 2022). Another preparation of A. gigas along with nine other herbs was tested clinically in two male cancer patients in Korea which remarkably suppressed the prostate cancer antigen (PSA) response patient and improved the quality of life for both (Lü et al, 2022).…”
Section: A Rapid Review Of the Clinical Trials Of Angelica Extractsmentioning
confidence: 99%